PENGGUNAAN FINE COAL SEBAGAI CAMPURAN PUPUK UREA DAN PENGARUHNYA TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomoea reptans) - Suryaputra, August; Nursanto, Edy; Winarno, Eddy (Jurnal Teknologi Mineral dan Batubara, 2024)
Fine coal is coal with a size of less than 0.5 mm which comes from processing waste or from avalanches during transportation using a conveyor belt. The aim of this research is to utilize fine coal as a mixture of plant fertilizer based on plant growth. There are four fertilizer treatments, namely 100% urea (UTB); 25% urea : 75% fine coal (UB13); 50% urea : 50% fine coal (UB11); and 75% urea: 25% fine coal (UB31) with nitrogen values ​​of 46%, 19.86%, 32.51% and 20% respectively. The average growth results in the form of number of leaves for each treatment were 10.6 strands, 10.9 strands, 9.8 strands and 8.5 strands, respectively. The average plant height in each treatment was 16.2 cm, 16.8 cm, 13.5 cm and 13.8 cm, respectively. The average nitrogen use efficiency (NUE) values ​​for each treatment were 27%, 19.6%, 25.9% and 10.5%, respectively. Plant growth experiments using a mixture of urea and fine coal fertilizer for number of leaves and plant height showed good results in the UB13 treatment, while NUE showed the best results in the UTB treatment.